Institutional Repository KTISIS: Research Evaluation and Promotion Tool - Zervas, Marios; Artemi, Petros; Veranis, George (My University, 2024)
The continuous development of the KTISIS institutional repository and the constant adaptation of its services to the needs of the Cyprus University of Technology (CUT) following the international trends and perspectives make KTISIS a pioneer in the world of institutional repositories. KTISIS allows researchers to include their research activities in their repository account. The adoption of a Performance-Based Research Fund (PBRF) by the University for the funding of researchers through criteria related to their activities and the new functionality allowing them through a bibliometric tool to generate their CV based on the Cyprus Quality Assurance and Accreditation Agency for Higher Education (CYQAA) standard make KTISIS a tool for their evaluation and promotion. KTISIS shows the metrics of research impact from various bibliographic databases and the alternative impact of research on the Social Network, thus providing researchers and authorities with a direct insight into research interest worldwide, giving them the opportunity to react and increase interest and opportunities for future collaborations. The article highlights all the efforts of the CUT Library to enhance research and assist its community in its efforts to promote research and find new opportunities for future collaborations.
Keywords: Current research information systems (CRIS); Bibliometrics; Research evaluation